1993
DOI: 10.1126/science.8211117
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte P Antigen: Cellular Receptor for B19 Parvovirus

Abstract: The pathogenic human parvovirus B19 replicates only in erythroid progenitor cells. This virus was shown to bind to blood-group P antigen, as measured by hemagglutination. Erythrocytes lacking P antigen were not agglutinated with B19. Purified P antigen (globoside) blocked the binding of the virus to erythroid cells and the infectivity of the virus in a hematopoietic colony assay. Target cells were protected from infection by preincubation with monoclonal antibody to globoside. Knowledge of a parvovirus recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
433
0
16

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 781 publications
(452 citation statements)
references
References 20 publications
3
433
0
16
Order By: Relevance
“…This tropism is because of Globoside (erythrocyte P antigen) that acts as receptor for the virus [15]. Other than erythroid progenitors, globoside is also present on placenta, fetal myocardium, some megakaryocytes and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This tropism is because of Globoside (erythrocyte P antigen) that acts as receptor for the virus [15]. Other than erythroid progenitors, globoside is also present on placenta, fetal myocardium, some megakaryocytes and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In search of a mechanism of parvovirus-associated pancytopenia in a patient with HS, Hanada et al [15] showed that the incubation of bone marrow with parvovirus-containing serum significantly inhibits erythroid (CFU-E), myeloid (CFU-GM), and megakaryocytic (CFU-Mgk) growth. The inhibition of the erythroid precursors was most pronounced [15], and the erythroid P antigen (globoside), the site of viral entry into erythroid precursors, certainly mediates this preferential toxicity [16].…”
Section: Discussionmentioning
confidence: 99%
“…One such infection is caused by human parvovirus B19, a single-stranded DNA virus with tropism for erythroid progenitor cells [1]. While it has been believed that hematopoietic cell infection with parvovirus B19 is strictly confined to the erythroid series, viral growth can also be maintained in fetal liver cell cultures, and, in a case of pancytopenia after bone marrow transplantation, the parvovirus B19 capsid antigen has been detected within giant bone marrow granulocytes [2].…”
Section: Introductionmentioning
confidence: 99%